The YES Holiday Job Rush Campaign : Getting Montreal's Youth into the Workforce - Youth Employment Services (YES) (2009)

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)

YES E-News : April 2009 - Youth Employment Services (YES) (2009)

A Policy Framework for Economic Development and Employability for the English-speaking Communities of Quebec : Submitted to the Quebec Community Groups Network (QCGN) - Qu'anglo (2008)
Through previous research and following a number of community consultations, the QCGN had determined that there is a need for initiatives that will enable the English-speaking Communities of Quebec to work more effectively with the Government of Canada, the Government of Quebec, school boards and relevant stakeholders to more fully participate in the economy of province. Given the continuing exodus of educated and trained anglophones to seek employment opportunities elsewhere, and the difficulties faced by particular segments of the population, especially youth, visible minorities and newly arrived immigrants, who choose to seek employment and self-employment within Quebec, it was determined that an integrated and targeted approach to improve the economic development prospects of the community was required.
Keywords: Official Language Minority Community (OLMC)

YES E-News : September 2007 - Youth Employment Services (YES) (2007)

Creating Sustainable Initiatives to Retain and Maintain Health and Social Services Professionals on the Lower North Shore - Lavallée, Marissa (Coasters Association, 2007)
The Coasters Association, in partnership with the Centre de Sant et de Services Sociaux de la Basse-C te-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University, for seven weeks from February 13th to March 31st, 2006, Phase 1, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining English Professionals on the Lower North Shore. The objective of this needs assessment was to develop Phase II which is a two-year proposal that would lead to the improvement of hiring and retaining Health and Social Services Professionals on the Lower North Shore. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the territory. Another objective of this needs assessment is to contact institutional and community-based objectives (i.e Education & Health and Social Services) it is hoped that these contacts will lead to partnerships that will help to address the hiring and retention of English-speaking Professionals on the Lower North Shore.

Special Needs Project - Lavallée, Marissa (2007)

Self-Employment and Employment in Quebec's English-speaking Cultural Communities and Visible Minorities : Prospects and Problems - Jedwab, Jack (Youth Employment Services (YES), 2006)
What are the principal barriers to self-employment and employment for members of Quebec’s English-speaking visible minorities and cultural communities? The question is considered in this report in view of the ongoing challenges that some members of English-speaking visible minorities and cultural communities face in the current economy. The specific aim is to improve our understanding of factors which prevent members of Quebec’s English-speaking visible minorities and cultural communities from achieving self-employment and employment goals.

A Needs Assessment on the Issue of Hiring and Retaining English Professionals on the Lower North Shore - Coasters Association (2006)
The Coasters Association, in partnership with the Centre de Santé et de Services Sociaux de la Basse- Côte-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University for seven (7) weeks from February 13 to March 31, 2006, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining Professionals, not only English-speaking - but Bilingual Professionals as well, on the Lower North Shore of Quebec. The objective of this needs assessment was to develop Phase II which is a two year proposal that would lead to the improvement of hiring and retaining professionals on the territory. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the Lower North Shore. Another objective of this needs assessment is to make contact with institutional and community based organizations (ie: Education and H.&S.S.), it is hoped that these contacts will lead to long term partnerships and commitment to addressing the hiring and retention of English and/or Bilingual Professionals on the Lower North Shore.

BCRC Newsletter - Black Community Resource Centre (BCRC) (2006)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

BCRC Newsletter - Black Community Resource Centre (BCRC) (2005)

A Report on the Quebec Fishing Community Adjustment Measures (QFCAM) Project - Blanche, Diana (Coasters Association, 2003)
The following report is a compilation of information pertaining to the activities under taken by the participants of the Fishery Restructuring Program.

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

Alliance Quebec Presents Equity Brief to Quebec National Assembly - Alliance Quebec (AQ) (2000)

Brief on Draft Law Number 143 Equity in the Civil Service - Alliance Quebec (AQ) (2000)
As the Committee studying draft law 143 is aware, Alliance Quebec is an association which lobbies governments at all levels for the rights and needs of the Englishspeaking population of Quebec to be respected. Our organization has chapters in Montreal, West Island, East Island, South Shore, Laval, Rouyn-Noranda, Val d'Or, Saguenay Lac Saint Jean, Mauricie and the Upper and Lower Laurentians. We also have our provincial youth commission that represents young people province-wide. In all, over 83 percent of Quebec's English-speaking population resides in Alliance Quebec territory.

Conference on Job Equity and Employability - Johnson, William (2000)

A Brief on Quebec's English-speaking Youth on the Occasion of the Youth Summit - Alliance Quebec (AQ) (2000)
We, the English-speaking youth of Quebec, come before you today to ask that our distinctive voices be heard. We share many of the concerns, problems and preoccupations of our French-speaking brothers and sisters. But we have anguishes, specific and poignant, which are ours alone, and which you will not hear about from the other participants and observers at the Youth Conference.